Evaluating the Current State of the Life and Family Skills Curriculum for Third-Grade Intermediate Students in Light of Constructivist Theory Principles - Al-Maashouq, Nada AbdelAziz; Al-Shabl, Manal AbdelRahman (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to evaluate the current state of the Life and Family Skills curriculum for third-grade intermediate students in Saudi Arabia in light of constructivist theory principles. The study employed a descriptive-analytical method using content analysis. The sample consisted of the Life and Family Skills textbook for the academic year 1446 AH. A content analysis tool was developed based on constructivist theory principles, which included five dimensions: prior knowledge, self-constructed knowledge, cognitive structure change, problem-solving, and social negotiation. The results revealed that including constructivist principles in the textbook content was low, with percentages ranging from 1% to 14%. The study recommended reorganizing the curriculum content according to constructivist principles, training teachers to apply these principles, and conducting future studies to develop curricula.
Keywords: Constructivist theory; life skills; family education; content analysis; curriculum development; active learning; education in Saudi Arabia